2017
DOI: 10.1007/5584_2017_62
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nephrin Phosphorylation in Diabetes and Chronic Kidney Injury

Abstract: Diabetes is the leading cause of microalbuminuria and end-stage renal failure in industrial countries. Disruption of the filtration barrier, seen in almost all nephrotic diseases and diabetes, is the result of the loss or effacement of the podocyte foot process, notably damage of proteins within the slit diaphragm such as nephrin. For many years, nephrin has been viewed as a structural component of the slit diaphragm. It is now well recognized that nephrin contains several tyrosine residues in its cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Foot process fusion caused by podocyte injury is the main mechanism of glomerular proteinuria. 16,17 Clinical studies have shown that podocyte injury appeared in the early stage of the disease, and was accompanied by podocyte retraction, widening, fusion, and disappearance. Additionally, kidney biopsies of DN patients and animal models showed foot process disappearance and a decrease in podocytes by concomitant degrees of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Foot process fusion caused by podocyte injury is the main mechanism of glomerular proteinuria. 16,17 Clinical studies have shown that podocyte injury appeared in the early stage of the disease, and was accompanied by podocyte retraction, widening, fusion, and disappearance. Additionally, kidney biopsies of DN patients and animal models showed foot process disappearance and a decrease in podocytes by concomitant degrees of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, C1-Ten is upregulated in diabetic nephropathy (DN) models and is associated with induction of podocyte hypertrophy ( 99 ). Increased levels of SHP-1 phosphatase have likewise been identified in models of DN ( 74 , 94 98 ) resulting in reduced phosphorylation of Y1176, Y1193, and Y1217, and disruption of nephrin and Nck binding. These recent findings position global reductions in nephrin tyrosine phosphorylation as a mechanism of damage in DN, the most common form of CKD.…”
Section: Phosphatase-mediated Regulation Of Nephrin Tyrosine Phosphormentioning
confidence: 94%
“…PTP-1B, which is upregulated in the puromycin aminonucleoside (PAN) model of membranous nephropathy (MN), can directly dephosphorylate rat tyrosine residues that correlate to the human sites 1193 and 1217 ( 67 ). Likewise, the SHP-1 phosphatase, which binds group A tyrosine residues, dephosphorylates tyrosines 1176, 1193, and 1217 ( 74 ) and its upregulation has been observed in instances of hyperglycemia and diabetes by several groups ( 74 , 94 98 ). In podocytes, hyperglycemia induces a persistent increase in SHP-1 expression, due to epigenetic modification in the SHP-1 promoter ( 97 ), leading to insulin signaling resistance, podocyte dysfunction, and cell death.…”
Section: Phosphatase-mediated Regulation Of Nephrin Tyrosine Phosphormentioning
confidence: 99%
See 1 more Smart Citation
“…Severe injury of the slit diaphragm complex lead to loss or effacement of podocyte foot process and, which contributes to protein uric renal injury [4,5]. In addition, the disruption of the filtration barrier observed in diabetic nephrotic diseases, is due to damage of proteins within the slit diaphragm such as nephrin [6]. Accordingly, the podocytes can be a potential therapeutic target in diabetic nephropathy (DN).…”
Section: Introductionmentioning
confidence: 99%